The effect of black cumin oil (Nigella sativa) on the reproduction of male Wistar rats - Syahran Wael; didik wahyudi; Tayeb wael; Zaid Mohamed Jaber (Program Studi Pendidikan Biologi, Pascasarjana, Universitas Pattimura, 2021)
Nigella sativa oil is antioxidant compound has the effect that serves to prevent cellular damage. The effect of Nigella sativa oil in the motility and total count of spermatozoa wistar rats. Experimental research with the design of post test only control group design. Wistar rats consists of 24 head and divided into 4 groups consist of control and treatment group. The control group was distilled. The first treatment was of Nigella sativa oil everydays as much with dose 150 mg/kgbw, 250 mg/kgbw, and 350 mg/kgbw, for 16 days, . Statistic test for motility and count of sperm wistar rats use the Kruskal-Wallis followed by Mann Whitney test. Avarage value of motility in the control (21.67±9.832) its lower than treatment. In dose 350 mg/kgbw its highest (52.33±13.292) compare in the treatment 250 mg/kgbw (40.67±17.512) and 150 mg/kgbw (30.67±8.165). avarage value of count sperm in the control (130.83±41.877) its lower than treatments. In dose 350 mg/kgbw its highest (199.67±23.480) compare in the treatment 250 mg/kgbw (187.50±74.538) and 150 mg/kgbw (140.83±32.568). Administration of Nigella sativa oil occur to enhancement motility and number of spermatozoa wistar rats.